1997
DOI: 10.1037/0022-006x.65.3.405
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive—behavioral treatment of obsessive thoughts: A controlled study.

Abstract: TWenty-iiine patients with obsessive-compulsive disorder as diagnosed in accordance with the Diagnostic and Statistical Manual of Mental Disorders (3rd ed., revised; American Psychiatric Association, 1987) who did not have overt compulsive rituals were randomly assigned to treatment and waiting-list conditions. Patients in the treatment condition received cognitive-behavioral therapy consisting of a detailed explanation of the occurrence and maintenance of obsessive thoughts, exposure to obsessive thoughts, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
3
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(139 citation statements)
references
References 39 publications
(58 reference statements)
10
120
3
5
Order By: Relevance
“…In a case series, switching from an SSRI to the SNRI duloxetine was successful in a number of treatment-resistant patients (Dell'osso et al 2008). Two studies showed the superiority of CBT to a wait list condition (Cordioli et al 2003;Freeston et al 1997). Also, in children and adolescents, ERP was superior to a wait list (Bolton and Perrin 2008).…”
Section: )(E)mentioning
confidence: 99%
“…In a case series, switching from an SSRI to the SNRI duloxetine was successful in a number of treatment-resistant patients (Dell'osso et al 2008). Two studies showed the superiority of CBT to a wait list condition (Cordioli et al 2003;Freeston et al 1997). Also, in children and adolescents, ERP was superior to a wait list (Bolton and Perrin 2008).…”
Section: )(E)mentioning
confidence: 99%
“…It also contains exercises for their correction such as: identification and registration of automatic thoughts and dysfunctional beliefs, Socratic questioning about erroneous beliefs underlying obsessions or rituals, the search of alternative explanations or hypotheses, exercises to estimate the probability of occurring disasters, the cake (or pizza) technique to reassess the assignment of responsibility, behavioral tests and the use of reminders. [21][22][23][24][25]32 We used a set of 73 transparencies to support the psychoeducational explanations. Electronic copies of the manual and the transparencies are available under request.…”
Section: Development Of the Protocol And Standardization Of The Therapymentioning
confidence: 99%
“…Until recently the influence of erroneous beliefs in the origin, maintenance and severity of obsessive-compulsive symptoms was not considered and, therefore, not investigated. Several authors, however, have described cognitive dysfunctions in OCD, even though non-specific, 32 cognitive techniques for its correction, [21][22][23][24][25] and have also verified the relationship between the intensity of the dysfunctional beliefs and the intensity of the symptoms and the results of ERP therapy. 19 These techniques would be particularly useful in patients with predominance of obsessions or with obsessions without rituals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other anxiety disorders, a CBT approach to treatment of obsessions and compulsions that includes a strong CR component does lead to significant immediate and long-term symptom reduction (e.g., Freeston et al, 1997;McLean et al, 2001;van Oppen et al, 1995;Whittal, Robichaud, Thordarson, & McLean, 2008;Whittal, Thordarson, & McLean, 2005). Furthermore, it is apparent that CR alone can have a significant treatment effect even in the absence of systematic, intensive ERP (Cottraux et al, 2001;Whittal et al, 2005;Wilson & Chambless, 2005).…”
Section: Component Analysismentioning
confidence: 99%